Effects Workplace Stretching Exercise and Water Consumption Frequency on Fatigue Construction Workers Project X Surabaya - Pramudya, Dandy Arie; Sulistyorini, Anita; Marji, Marji; Ulfah, Nurnaningsih Herya (Jurnal Kesmas Jambi, 2026)
Worker fatigue contributes to approximately 60% of workplace accidents. Preliminary data from Project X Surabaya showed that 67% of workers experienced high fatigue, while 33% experienced moderate fatigue. This study aimed to analyze the effects of workplace stretching exercises and water consumption frequency on worker fatigue at Project X Surabaya. A quasi-experimental design with a two-group pretest–posttest approach was employed. Fatigue was measured using the Industrial Fatigue Research Committee (IFRC) questionnaire, a Digital Reaction Timer, and observation sheets, all of which had been validated. Data were analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test with a significance level of p < 0.05. The results indicated that both interventions significantly reduced worker fatigue, with the combined intervention of workplace stretching exercises and increased water consumption frequency producing greater effects than water consumption alone. These findings suggest that implementing stretching and hydration programs in the workplace may help reduce fatigue and support occupational health and safety. The study recommends establishing workplace policies that promote stretching exercises and adequate water consumption. Future research should involve larger sample sizes, longer intervention periods, and additional variables related to hydration practices.